DASAR PEMIKIRAN FILSAFATI PENGAMBANGAN DAERAH PARIWISATA - Saryani, Saryani (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2004)
Speaking about tourisme it needs to look the global correlation that the object and tourist. Infrastructure is needed for both. The negative and positive effect found in tourisme developing. That is why the does have to pay more attention in constructing beetwen tourisme and human sourounding and the creative.